Food, Faith, and Sustainability: Islamic Ethical Foundations for a Just and Ecological Future - Qudsia Firdous; Hafiz Muhammad Zahid Yasin (UIN Raden Mas Said Surakarta, 2025)
This paper examines Islamic food ethics as a holistic framework for addressing contemporary challenges of social justice, ecological sustainability, and interreligious harmony. Moving beyond a narrow understanding of halal as ritual permissibility, the study proposes an Ethical Halal model that integrates four interrelated principles: halal compliance, animal welfare, ecological sustainability (al-istidāmah), and social equity. Drawing on Qur’anic concepts of ṭayyib (pure and wholesome consumption), Prophetic teachings on moderation (wasatiyyah) and stewardship (khilāfah), and relevant contemporary scholarship, the article highlights the moral and transformative dimensions of Islamic dietary ethics.The analysis emphasizes three key themes. First, animal welfare, grounded in the Qur’anic recognition of animals as moral communities deserving compassionate treatment. Second, sustainability, articulated through prohibitions against waste (isrāf) and the promotion of environmental responsibility as a form of ongoing charity. Third, food-based charity, including zakāt and ṣadaqah, which functions to reduce inequality, alleviate hunger, and foster social and interfaith solidarity. Overall, the study demonstrates that food in Islam constitutes a site of worship, ethical responsibility, and ecological care. The Ethical Halal framework offers practical insights for policymakers, educators, and community leaders seeking sustainable and inclusive approaches to food ethics in a globalized world.